GAMBARAN TINGKAT PENGETAHUAN SISWA MADRASAH ALIYAH AR RISALAH TENTANG INFERTILITAS PRIA TAHUN 2022 - Maharani, Rifty Zhafira; Amir, Arni; Firdawati, Firdawati (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Background: The lack of research and knowledge about male infertility among men from adolescence to adulthood in Indonesia make people not aware of the incidence of infertility in the future and do not have time to take preventive measures. Objective: The purpose of the study was to describe the level of knowledge of Madrasah Aliyah Ar Risalah students about male infertility. Methods: This research used an observational descriptive with cross-sectional design. The research sample amounted to 144 people with Total Sampling. This research used primary data taken using a questionnaire. Results: This research indicated that respondents who had good knowledge were 14.6%, 66.7% were sufficient and 18.8% less. The majority of respondents with good knowledge are respondents aged 12-16 years, majoring in science, from outside the city of Padang and who get information from teachers. Conclusion: This research concluded that most of the students had sufficient knowledge about male infertility